Palliative radiation therapy (RT) for prostate cancer patients with bone metastases at diagnosis: A hospital‐based analysis of patterns of care, RT fractionation scheme, and overall survival. (17th August 2018) - Fischer‐Valuck, Benjamin W.; Baumann, Brian C.; Apicelli, Anthony; Rao, Yuan James; Roach, Michael; Daly, Mackenzie; Dans, Maria C.; White, Patrick; Contreras, Jessika; Henke, Lauren; Gay, Hiram; Michalski, Jeff M.; et al.
Abstract: Prostate cancer (PCa) is one of the most common malignancies associated with bone metastases, and palliative radiation therapy (RT) is an effective treatment option. A total of 2641 patients were identified with PCa and bone metastases at diagnosis from 2010 to 2014 in the NCDB. Fractionation scheme was designated as short course ([SC‐RT]: 8 Gy in 1 fraction and 20 Gy in 5 fractions) vs long course ([LC‐RT]: 30 Gy in 10 fractions and 37.5 Gy in 15 fractions). Patient characteristics were correlated with fractionation scheme using logistic regression. Overall survival was analyzed using the Kaplan‐Meier method, log‐rank test, Cox proportional hazards models, and propensity score‐matched analyses. A total of 2255 (85.4%) patients were included in the LC‐RT group and 386 (14.6%) patients in the SC‐RT group. SC‐RT was more common in patients over 75 years age (odds ratio [OR]: 1.70, 95% confidence interval [CI] 1.32‐2.20), treatment at an academic center (OR: 1.76, 1.20‐2.57), living greater than 15 miles distance to treatment facility (OR: 1.38, 1.05‐1.83), treatment to the rib (OR: 2.99, 1.36‐6.60), and in 2014 (OR: 1.73, 1.19‐2.51). RT to the spine was more commonly long course ( P < .0001). In the propensity‐matched cohort, LC‐RT was associated with improved OS ( P < .0001), but no OS difference was observed between 37.5 Gy and either 8 Gy in one fraction or 20 Gy in 5 fractions ( P > .5). LC‐ RT remains the most common treatment fractionation scheme for palliative bone metastases in PCa patients. Use of palliative SC‐RT is increasing, particularly in more recent years, for older patients, treatment at academic centers, and with increasing distance from a treatment center. Abstract : Fractionation schemes of over 10 treatments remain the most common palliative course of radiation for bone metastases in prostate cancer. The use of shorter courses of radiation is increasing, particularly for older patients, treatment at academic centers, and with increasing distance from a treatment center. Since publication of evidence‐based guidelines and the ASTRO "Choosing Wisely" campaign, the use short‐course radiation is also increasing, but remains underutilized.